The Limits of Modern Western Science (I) - Mickūnas, Algis (Sociologija. Mintis ir veiksmas, 2005)
Education, and above all formal education, has been one of the principle components of modernization and globalization. This is to say that the notion of universal participation in human affairs is by now regarded a necessary condition for national and international relationships and understanding. Without education, as a rational condition, such relationships and understanding are hardly possible. The call for extension of democracy and the production of the good life around the globe is constantly premised on the requirements of formal education. It is advisable to disclose what constitutes this modern education and what sort of human being and a type of reality does it require and in fact construct. While the phrase formal education sounds intellectual, indeed enlightening, we want to argue that such a designation has a preunderstanding that frames the modern Western civilizational understanding of sciences and by extension of human sciences. Indeed, it shapes the way in which human beings must become in their concrete, practical interrelationships, whether intra or international.
Keywords: education; democracy; globalization; multi-discursitvity